A multigeneration cascade system using ground-source energy with cold recovery: 3E analyses and multi-objective optimization. (15th October 2021) - Mahmoudan, Alireza; Samadof, Parviz; Hosseinzadeh, Siamak; Garcia, Davide Astiaso
Abstract: A novel integrated energy system based on a geothermal heat source and a liquefied natural gas heat sink is proposed in this study for providing heating, cooling, electricity power, and drinking water simultaneously. The arrangement is a cascade incorporating a flash-binary geothermal system, a regenerative organic Rankine cycle, a simple organic Rankine cycle, a vapor compression refrigeration cycle, a regasification unit, and a reverse osmosis desalination system. Energy, exergy, and exergoeconomic methods are employed to analyze the suggested system. A parametric study based on decision variables is carried out to better assess the system performance. Four different multi-objective optimization problems are also carried out. At the most excellent trade-off solution specified by the TOPSIS method, the system attains 29.15% exergy efficiency and 1.512 /GJ total product cost per exergy unit. The main output products are consequently calculated to be 101.07 kg/s cooling water, 570.44 kW net output power, and 81.57 kg/s potable water. Highlights: A multigeneration system utilizing a geothermal heat source and an LNG heat sink for HCP, and freshwater production. Multi-objective optimization based on thermodynamic and exergoeconomic analysis. Exergy efficiency of 29.15% and total product cost per exergy unit of 1.512 /GJ at the best trade-off solution. The highest achievable cooling water, net output power, and potable water of 101.07 kg/s, 570.44 kW, and 81.57 kg/s.